Exploring Dissolved Organic Carbon Variations in a High Elevation Tropical Peatland Ecosystem: Cerro de la Muerte, Costa Rica - Sanchez-Murillo, Ricardo (2022)
Tropical peatlands are distributed mainly in coastal lowlands; however high elevation regions exhibit a large prevalence of small and fragmented peatlands that are mostly understudied. Artificial drainage of peatlands to expand the area of cattle farming, horticulture, and urbanization is increasing carbon losses to the atmosphere and streams worldwide. Here, we present an exploratory characterization of dissolved carbon optical properties in ombrotrophic peat bogs of the Talamanca range of Costa Rica, across an altitudinal gradient (2,400–3,100 m a.s.l.) during the rainy season. Dissolved organic matter (DOM) sources and decomposition processes were evaluated in the light of dissolved organic and inorganic carbon (DOC and DIC), optical properties, and major water chemistry. DOC concentrations ranged from 0.2 up to 47.0 mg/L. DIC concentrations were below 2 mg/L and δ13CDIC values indicated a mixture between soil organic matter, CO2 in soil water, and to a lesser degree DIC derived from bacterial CO2. Absolute fluorescence intensity of humic-like peaks was 6–7 times greater than fresh-like peaks across all sites. Fluorescence peak ratios coupled with the biological and humification indexes point to a greater relative contribution of recalcitrant soil-derived DOM. Excitation/Emission matrices denoted a high prevalence of humic and fulvic acids in the peat bogs, with moderate intensities in soluble microbial by-products-like and aromatic protein regions at three sites. Our data provides a baseline to underpin tropical carbon dynamics across high elevation peatlands.